2016
DOI: 10.1007/s00455-016-9699-5
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Two Tongue-Pressure Resistance Training Protocols for Post-Stroke Dysphagia

Abstract: The objective of this study was to compare the outcomes of two tongue resistance training protocols. One protocol (“Tongue-Pressure Profile Training”) emphasized the pressure-timing patterns that are typically seen in healthy swallows by focusing on gradual pressure release and saliva swallowing tasks. The second protocol (“Tongue-Pressure Strength and Accuracy Training”) emphasized strength and accuracy in tongue-palate pressure generation and did not include swallowing tasks. A prospective, randomized, paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
137
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(152 citation statements)
references
References 43 publications
7
137
1
7
Order By: Relevance
“…The results of anterior tongue pressure obtained in this study were similar to those found in studies using the IOPI in the Korean (26) and American (14) populations. Those with the posterior pressure were similar to a survey of Canadian subjects (27) , however, lower than those previously mentioned, which shows that this data can vary according to the characteristics of each population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of anterior tongue pressure obtained in this study were similar to those found in studies using the IOPI in the Korean (26) and American (14) populations. Those with the posterior pressure were similar to a survey of Canadian subjects (27) , however, lower than those previously mentioned, which shows that this data can vary according to the characteristics of each population.…”
Section: Discussionsupporting
confidence: 83%
“…In 2013, the Toronto Rehabilitation Institute's Swallowing Rehabilitation Research Laboratory presented a tongue pressure profile training protocol developed specifically for the treatment of dysphagia affecting post-stroke patients (30) and, in 2016, this group published an article comparing the results of this training protocol, which involves muscular training and swallowing, along with another type of training, only muscular, without function training. After an average of 16 sessions, both post-stroke patients with dysphagia and those without dysphagia achieved significant strength gain, accompanied by an improvement in swallowing in some cases, but without a significant difference between the groups (27) . Some limitations could be verified in the development of this study, such as the size of some strata and, especially, the degree of dysphagia (absence of a patient with severe dysphagia).…”
Section: Discussionmentioning
confidence: 90%
“…Tongue‐strength was reduced into a categorical measure (weak versus within normal range), with a boundary of one standard deviation below the sample mean for maximum isometric tongue pressure (i.e., 40.51 kPa) used to delineate these two categories. This value corresponds to the clinical cut‐off of 40 kPa that has been used in previous clinical trials research for determining whether or not a patient exhibits tongue weakness (Steele et al, ). Age‐group was similarly reduced to a categorical measure (under 70 versus 70 or older).…”
Section: Methodsmentioning
confidence: 99%
“…Eighteen studies 4,9,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] were included in our analysis, totalling 374 adults ( Table 1). Ten of the 18 studies targeted healthy adults, 4,9,12,[14][15][16][17][18][19][20] while the other eight studies [21][22][23][24][25][26][27][28] targeted patients with dysphagia. In studies involving healthy individuals, two studies compared tongue strength training vs. a non-exercise control group, 12,14 six studies were composed of only a tongue strength training group, 4,15,16,[18][19][20] one study had two different tongue strength training interventions, 17 and one study compared three different tongue strength interventions and an exercise control group (lip compression).…”
Section: Included Studies and Participant Characteristicsmentioning
confidence: 99%
“…9 Seven studies involving patients with dysphagia compared therapy interventions vs. tongue strength training plus therapy interventions. [22][23][24][25][26][27][28] Participants of six of the eight studies involving dysphagia were stroke survivors. 21,23,[25][26][27][28] All studies 4,9,12,14-28 involved men and women; however, it was not possible to identify the number of men and women in each intervention group in three studies 12,17,22 (Table 1).…”
Section: Included Studies and Participant Characteristicsmentioning
confidence: 99%